2018
DOI: 10.1002/2017ja025131
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Intermittency‐Induced Critical Dynamics in Geomagnetic Field Time Series Prior to the Intense Magnetic Storms of March, June, and December 2015

Abstract: Criticality has been proposed as a suitable framework to study the nonlinear system of the Earth's magnetosphere. The magnetic field variations observed by the midlatitude HellENIc GeoMagnetic Array with respect to the most intense magnetic storms (Dst <− 150 nT) of the current solar cycle (i.e., 17 March, 23 June, and 20 December 2015) are analyzed using the method of critical fluctuations. We show that the application of method of critical fluctuation to the HellENIc GeoMagnetic Array time series reveals the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
(98 reference statements)
0
19
0
Order By: Relevance
“…Specifically, Sitnov et al () suggested that while the multiscale activity during substorms resembles second‐order phase transitions, the largest substorm avalanches exhibit common features of first‐order nonequilibrium transitions. Moreover, Balasis et al (, ) demonstrated the existence of two different regimes in the magnetospheric dynamics associated with the prestorm activity and magnetic storms, respectively, a picture that is compatible with the occurrence of a phase transition. Another intense point of research is the inherent separation of timescales between internal and externally driven/triggered processes (e.g., Alberti et al, ; Consolini & De Michelis, ; Kamide & Kokobun, ; Tsurutani et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, Sitnov et al () suggested that while the multiscale activity during substorms resembles second‐order phase transitions, the largest substorm avalanches exhibit common features of first‐order nonequilibrium transitions. Moreover, Balasis et al (, ) demonstrated the existence of two different regimes in the magnetospheric dynamics associated with the prestorm activity and magnetic storms, respectively, a picture that is compatible with the occurrence of a phase transition. Another intense point of research is the inherent separation of timescales between internal and externally driven/triggered processes (e.g., Alberti et al, ; Consolini & De Michelis, ; Kamide & Kokobun, ; Tsurutani et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…The obtained results show that the ULF magnetic field data of the ENIGMA magnetometer array, beyond their primary use for the study of space weather and extreme space weather events, such as magnetic storms [ 50 ], can be efficiently employed for the detection of possible precursors of seismic activity by applying advanced analysis methods. Moreover, the fusion of the information obtained from these ULF magnetic field data with information from other kinds of EM data, such as subionospheric VLF/LF (low frequency) propagation data (ionospheric perturbations), ionosonde data, satellite data, fracto-EME (MHz, kHz) signals, SES signals, etc., but also gas emanation data, such as radon concentrations in boreholes, as well as tectonic information, seismic zonation, and foreshock seismic activity data, may: (a) help deciphering the physical mechanisms that are related to different seismo-electromagnetic phenomena (e.g., elucidating the LAI coupling mechanism) and (b) contribute to a future multi-parametric seismic risk assessment system.…”
Section: Discussionmentioning
confidence: 99%
“…According the NOAA SWPC, the two CMEs appeared to have merged in the interplanetary medium, impacting the Earth at 15:28 UT on 19 December 2015. The flare and propagation of these CMEs have been discussed in published papers (e.g., Balasis et al, 2018; Liu et al, 2018), but due to their differing perspectives, these papers give slightly different accounts of the transits of these disturbances through interplanetary space. As we are concerned with the resulting geomagnetic activity, we will use the archived NOAA SWPC reports to establish a timeline for the 22 December 2015 EMIC wave events in the context of the storm.…”
Section: Space Weather Context For the Emic Wave Observationsmentioning
confidence: 99%
“…The 19–22 December 2015 storm was a significant and complex event that has been mentioned in several papers on the effects of space weather. These papers have examined the scintillation of transionospheric radio signals (Chashei et al, 2016; Loucks et al, 2017; Wang et al, 2018; Zakharenkova & Cherniak, 2018), the ionospheric total electron content (TEC) (Blagoveshchensky et al, 2018; Mansilla, 2019), geomagnetically induced currents (GIC) in the Irish power network (Blake et al, 2016), and the response of the magnetosphere as a nonlinear system (Balasis et al, 2018). This storm has also been mentioned in papers using Van Allen Probes data, including a study of impulsive electric fields associated with interplanetary shocks (Zhang et al, 2018), a study of whistler mode chorus with tones that oscillate in frequency (Gao et al, 2017), and a survey of radiation belt enhancements observed by the Van Allen Probes from October 2012 to April 2017 (Boyd et al, 2018).…”
Section: Space Weather Context For the Emic Wave Observationsmentioning
confidence: 99%